2006
DOI: 10.1002/nau.20245
|View full text |Cite
|
Sign up to set email alerts
|

Negative impact of urinary incontinence on quality of life, a cross‐sectional study among women aged 49–61 years enrolled in the GAZEL cohort

Abstract: UI affects QoL even among women from a nonclinical population, and the more severe the UI, the more harmful the effect. These results raise the question of whether UI in its severe forms should be considered a disability because of its negative effects on mobility in daily life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0
7

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 33 publications
2
45
0
7
Order By: Relevance
“…16,31 However, obese women consistently reported a higher degree of impaired quality of life attributed to incontinence in comparison to nonobese controls. The greatest differences were noticed in the domains of emotional health and feelings of frustration.…”
Section: Discussionmentioning
confidence: 99%
“…16,31 However, obese women consistently reported a higher degree of impaired quality of life attributed to incontinence in comparison to nonobese controls. The greatest differences were noticed in the domains of emotional health and feelings of frustration.…”
Section: Discussionmentioning
confidence: 99%
“…These questions are similar to those of the Sandvik score, which is often used in epidemiological surveys addressing UI. 4,12 The third question assesses how much these leaks interfere with everyday life. The ICIQ-SF score is calculated from the answers to these three questions; it ranges between 0 and 21 and is correlated with the pad test.…”
Section: Methodsmentioning
confidence: 99%
“…10 Urinary incontinence has been found to affect quality of life even among women from a non-clinical population, and the more severe the urinary incontinence, the more harmful the effect. 11 Lam et al 12 reported that 19% of incontinent women abstained from some form of social activities, such as visiting friends, sport, shopping or going to work. All these findings emphasize the fact that urinary incontinence, urgency and frequency have a great psychological and social impact on a woman's daily life.…”
Section: Discussionmentioning
confidence: 99%